The Meaning and Measurement of Aggregate Technical Change - Dan Usher (Queen's University, Department of Economics, 1969)
It has been observed by many that Jorgenson and Griliches' findings have profound implications about the nature and prospects of economic development. In this paper, the author proposes to show that Jorgenson and Griliches' evidence does not bear these implications, and that the inferences drawn from the earlier studies were largely correct.
Keywords: 330